Pengembangan Permainan Interaktif untuk Meningkatkan Kosakata Bahasa Jerman Level A1 dengan Menggunakan Game Construct 2 - Simaremare, Yuni Melati Anestasya; Br Sitanggang, Elfretty; Onyx Nifty; Roihan Anwar; Tarigan, Jenda Rizkinta; Surya Yusuf; Hutagalung , Surya Masniari; Harahap, Ahmad Bengar (Pusat Riset dan Inovasi Nasional, 2025)
In German language courses at universities, students must learn four skills: reading, writing, listening, and speaking. To master these four skills, students must have a good command of vocabulary, as this is the foundation needed to master the German language. This software does not require programming code, so users can easily add graphics and sounds to the game. Without vocabulary, skills such as reading, writing, speaking, and listening cannot be performed. This study aims to create a Construct 2 application that can be used by college students to increase their A1 level German vocabulary. The data for this study is A1 level German vocabulary with the theme “Guten Appetit,” and another source of data is the book “Netzwerk neu A1 Kursbuch” published by Ernst Klett Sprachen GmbH in 2019. This research will be conducted in the foreign language laboratory at UNIMED. The application will be tested by subject matter experts and learning media experts. This research will be published in a nationally indexed journal.